2002
DOI: 10.1046/j.1365-2354.2002.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the needs of people using a cancer information service in Northern Ireland

Abstract: A retrospective analysis of first-time enquirers using a cancer information service in Belfast, Northern Ireland, is presented. Our results show that women are three times more likely to use the service than men, with relatives and friends more likely to seek information on behalf of cancer patients than patients themselves. Unlike patients with cancer at other sites, the number of enquiries from breast cancer patients [standard incidence rate (SIR) = 1.5] was greater than incidence figures for the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
1
14
0
2
Order By: Relevance
“…This study and others (Mills & Davidson 2002) have shown that patients clearly want access to information that is easy to understand and delivered in a timely and sensitive manner (Department of Health, NHS Executive 2002; NICE 2004). As such, the provision of information often becomes the responsibility of families, friends and those close to the patient as well as the voluntary-sector support groups and helplines (Manning & Quigley 2002). As such, the provision of information often becomes the responsibility of families, friends and those close to the patient as well as the voluntary-sector support groups and helplines (Manning & Quigley 2002).…”
Section: Resultsmentioning
confidence: 99%
“…This study and others (Mills & Davidson 2002) have shown that patients clearly want access to information that is easy to understand and delivered in a timely and sensitive manner (Department of Health, NHS Executive 2002; NICE 2004). As such, the provision of information often becomes the responsibility of families, friends and those close to the patient as well as the voluntary-sector support groups and helplines (Manning & Quigley 2002). As such, the provision of information often becomes the responsibility of families, friends and those close to the patient as well as the voluntary-sector support groups and helplines (Manning & Quigley 2002).…”
Section: Resultsmentioning
confidence: 99%
“…1993, 2002; Lechner & De Vries 1996; Boudioni et al . 1999; Manning & Quigley 2002). Additionally, like previous observations, diagnosed cancer patients were the minority of callers (Wilkinson & Wilson 1983; Rainey 1985; Slevin et al .…”
Section: Discussionmentioning
confidence: 99%
“…1996; Boudioni et al . 1999; Manning & Quigley 2002) no previous reports have described the operation of an Australian service. Thus, the broad aims of the present evaluation were, firstly, to describe the information and support needs of callers to the Cancer Helpline and, secondly, to describe the response of the service to callers’ needs.…”
Section: Introductionmentioning
confidence: 99%
“…Results of a study to determine the experience and needs of people affected by cancer indicate 68% of participants (n=178/262) reported as overwhelming the written information provided to them in a consultation [24]. Evidence from a descriptive study to understand the needs of people using a cancer information service indicates persons affected by cancer may not fully comprehend medical terms used in a medical consultation and require further explanation to maximise their understanding [23]. Providing those affected by cancer with tailored and individualised information is demanding, requiring a high level of communication capability [6,13,28].…”
Section: Introductionmentioning
confidence: 99%